Donor-recipient sex is associated with transfusion-related outcomes in critically ill patients - Alshalani A. (2023)
Transfusion of red blood cells (RBCs) from female donors has been associated with increased risk of mortality. This study aims to investigate the associations between donor-recipient sex and posttransfusion mortality and morbidity in critically ill patients who received RBC transfusions from either male-only donors or from female-only donors (unisex-transfusion cases). Survival analysis was used to compare 4 groups: female-to-female, female-to-male, male-to-female, and male-to-male transfusion. Multivariate logistic model was used to evaluate the association between donor sex and intensive care unit (ICU) mortality. Associations between transfusion and acute kidney injury (AKI), acute respiratory distress syndrome (ARDS), and nosocomial infections were assessed. Of the 6992 patients included in the original cohort study, 403 patients received unisex-transfusion. Survival analysis and the logistic model showed that transfusion of female RBCs to male patients was associated with an increased ICU mortality compared with transfusion of female RBCs to female patients (odds ratio, 2.43; 95% confidence interval, 1.02-5.77; P <.05). There was a trend toward increased ARDS in patients receiving RBC from female donors compared with those receiving blood from males (P = .06), whereas AKI was higher in donor-recipient sex-matched transfusion groups compared with sex-mismatched groups (P = .05). This was an exploratory study with potential uncontrolled confounders that limits broad generalization of the findings. Results warrant further studies investigating biological mechanisms underlying the association between donor sex with adverse outcomes as well as studies on the benefit of matching of blood between donor and recipient.